2016
DOI: 10.1021/acsphotonics.6b00213
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Raman Enhancement on Monolayer MoS2

Abstract: Surface-enhanced Raman scattering (SERS) is commonly associated with noble metal substrates. However, over the years modest Raman enhancements (<104) have also been observed in semiconductor substrates. This enhancement stems predominantly from the excitonic resonance of the semiconductors. The use of two-dimensional semiconductors with large excitonic oscillator strength provides an attractive pathway to further enhance this effect. Here we report for the first time a >3 × 105 enhancement in SERS signal from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
130
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 27 publications
(52 reference statements)
4
130
0
1
Order By: Relevance
“…The number of molecules contributing to SERS enhancement on the surface of QOS is based on the following assumptions: (i) The first layer of QOS contributes to observed SERS enhancement, (ii) The molecules adsorbed on the surface of QOS lie parallel to the surface. This is confirmed by the presence of symmetric modes in the SERS spectra including out-of-plane C-H deformation, ring deformation, in-plane C-H bending vibration, ring stretch vibration 54 . This assumptions is further confirmed by DFT calculations provided in the literature 56 .…”
Section: Methodsmentioning
confidence: 56%
“…The number of molecules contributing to SERS enhancement on the surface of QOS is based on the following assumptions: (i) The first layer of QOS contributes to observed SERS enhancement, (ii) The molecules adsorbed on the surface of QOS lie parallel to the surface. This is confirmed by the presence of symmetric modes in the SERS spectra including out-of-plane C-H deformation, ring deformation, in-plane C-H bending vibration, ring stretch vibration 54 . This assumptions is further confirmed by DFT calculations provided in the literature 56 .…”
Section: Methodsmentioning
confidence: 56%
“…They found size‐ and wavelength‐dependent resonances within the system, and attributed these charge‐transfer resonances to the basic causes of enhanced Raman spectroscopy. Moreover, the clearly enhanced Raman signals of 4‐MPY molecules on a two‐dimensional (2D) MoS 2 monolayer were reported by Muehlethaler et al . They obtained a high EF of 3×10 5 for 4‐MPY molecules placed on a MoS 2 monolayer.…”
Section: Sers‐active Semiconductor Nanomaterialsmentioning
confidence: 74%
“…Furthermore, by utilizing the amorphous structure to modulate the band structure of semiconductor substrates, we successfully improved the vibronic coupling of resonances in the substrate–molecule system. It is well known that when the dimension changes from 3D to 2D, the larger specific surface area and lower coordination number of the surface atoms enhances the reactivity of surface atoms towards molecules and increases the molecular polarizability . However, the ensuing wide band gap and discontinuous band structure in 2D nanomaterials severely limit the vibronic coupling of resonances, which deteriorate the PICT resonance.…”
Section: Sers‐active Semiconductor Nanomaterialsmentioning
confidence: 99%
“…Investigations on the semiconductor and graphene substrates indicated that Raman signal amplification of the molecules adsorbed on nonmetal component is mainly from chemical enhancement contribution, such as charge transfer effect . Lombardi and Birke derived an expression of SERS contributions for molecule‐semiconductor system, which successfully identified the enhancement arising from various resonances . So far, few research studies have been presented base on quantum chemical calculations for GERS and G‐SERS process due to huge challenges in modeling molecule‐graphene structure (including cluster model and Periodic model) and corresponding charge transfer effect during SERS process.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Lombardi and Birke derived an expression of SERS contributions for molecule-semiconductor system, which successfully identified the enhancement arising from various resonances. [20,21] So far, few research studies have been presented base on quantum chemical calculations [22] for GERS and G-SERS process due to huge challenges in modeling molecule-graphene structure (including cluster model and Periodic model) and corresponding charge transfer effect during SERS process.…”
Section: Introductionmentioning
confidence: 99%